2017
DOI: 10.1160/th17-08-0555
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Antithrombotic Treatment for Atrial Fibrillation: Insights from the GLORIA-AF Phase II Registry

Abstract: Introduction  Although guideline-adherent antithrombotic therapy (ATT) for stroke prevention in atrial fibrillation (AF) is associated with lower mortality and thromboembolism, ATT uptake shows geographic variation worldwide. We aimed to assess thromboembolic risk and baseline ATT by geographic region and identify factors associated with prescription of ATT in a large, truly global registry of patients with recently diagnosed AF. Methods and Results  Our analysis comprises 15,092 patients newly diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 42 publications
5
67
0
1
Order By: Relevance
“…Similarly, data from the GLORIA‐AF registry showed that AF guideline adherence requires improvement, as nearly half of low‐risk patients are overtreated, and that patients at high risk of stroke were undertreated with oral anticoagulants . Studies from Larock et al McDonald et al and Chowdry et al also reported high values of potentially inappropriate dabigatran prescriptions (31.2–51.1%), which corroborates the problem of off‐label doses with dabigatran.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, data from the GLORIA‐AF registry showed that AF guideline adherence requires improvement, as nearly half of low‐risk patients are overtreated, and that patients at high risk of stroke were undertreated with oral anticoagulants . Studies from Larock et al McDonald et al and Chowdry et al also reported high values of potentially inappropriate dabigatran prescriptions (31.2–51.1%), which corroborates the problem of off‐label doses with dabigatran.…”
Section: Resultsmentioning
confidence: 86%
“…In the setting of moderate, mild or no renal impairment, off-label use of the 75 mg dose might result in underdosed patients and may explain why no differences were observed in risk of ischaemic stroke, major gastrointestinal bleeding or mortality between warfarin and the lower dose of dabigatran. This was also seen in a retrospective study conducted in Japan,37 where 54 patients from 228 (23.7%) presented inappropriate dabigatran prescriptions.Similarly, data from the GLORIA-AF registry showed that AF guideline adherence requires improvement, as nearly half of low-risk patients are overtreated, and that patients at high risk of stroke were undertreated with oral anticoagulants 65. Studies from Larock et al 66 McDonald et al 67 and Chowdry et al 68 also reported high values of potentially inappropriate dabigatran prescriptions (31.2-51.1%), which corroborates the problem of off-label doses with dabigatran.…”
mentioning
confidence: 88%
“…In addition, a model estimating the effect of gender when adjusting for all other factors has been reported; 34 the effect of gender on anticoagulation was not affected by the adjustments (relative risk of anticoagulant prescription for females compared with males: 0.99 unadjusted vs. 0.99 adjusted for all other factors). We have therefore no reason to suspect that our results were sensitive to this choice.…”
Section: Limitationsmentioning
confidence: 99%
“…Similarly, the efficacy of NOACs has been also reported, but the evidence for the NOACs remains relatively scarce due to the relatively small number of studies. This is important to give the increasing widespread use of NOACs in clinical practice, in most regions of the world …”
Section: Current Management Of Af Patients With Latmentioning
confidence: 99%